1958
DOI: 10.1139/v58-079
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamics of Mutarotation of Some Sugars: Ii. Theoretical Considerations

Abstract: iln il~terpretatio~~ of A H ancl A S for the nu tarot at ion of D-glucose, D-uylose, maltose, ldctosc, and ccllobiosc is given in terms of changes in the hydmtion of the reducing 11)1clro\yl group I n this part of the paper we shall attempt to give an iilterpretation of the experirneiltal results shown in Table I and Fig. 4 of Part I." We shall first consider the conformations of the sugars used in I'art I and note that in all of them the neighboring groups of the reducing carbon are identical.There is a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
5

Year Published

1964
1964
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 15 publications
(12 reference statements)
5
56
0
5
Order By: Relevance
“…The differences (so-called A-values) seem greater in protic solvents (3, p. 236) ; 0.8 (7370 aqueous acetic acid), 0.9 (water), 0.96 (isopropanol), 1.25 (deuterium oxide) (28). This change in A-value on change from aprotic to protic solvents has been assigned t o solvation phenomena (38,39). For the purpose of illustrating the present status of our appreciation of the conformation of the trans-diol, it is useful t o assume average A-values for the hydroxyl group of 0.6 kcal/mole (aprotic solvent) and 1.0 kcal/mole (protic solvent).…”
Section: Cis-compoundsmentioning
confidence: 95%
“…The differences (so-called A-values) seem greater in protic solvents (3, p. 236) ; 0.8 (7370 aqueous acetic acid), 0.9 (water), 0.96 (isopropanol), 1.25 (deuterium oxide) (28). This change in A-value on change from aprotic to protic solvents has been assigned t o solvation phenomena (38,39). For the purpose of illustrating the present status of our appreciation of the conformation of the trans-diol, it is useful t o assume average A-values for the hydroxyl group of 0.6 kcal/mole (aprotic solvent) and 1.0 kcal/mole (protic solvent).…”
Section: Cis-compoundsmentioning
confidence: 95%
“…In dimethyl sulfoxide, the hydrogenbonding pattern should be different; based on the chemical shifts of hydroxyl protons, both axial and equatorial groups are strongly bonded by this solvent (1,5,16,17). Hence, if the OH-2 group of mannose (or OH-4 of arabinose) were now to be reoriented away from the molecule by association with the solvent, the oxygen orbitals should become directed inwards (3). Molecular models suggest that this arrangement .vvould increase repulsive interactions between these orbitals and the erected para orbital of the ring oxygen (see ref.…”
Section: That P-d-7rzannose I S Stabilized By Conzplexing Witlt Dimetmentioning
confidence: 99%
“…I t was surmised initially that water might selectively stabilize pyranose forms of some of the sugars by hydrogen bonding, and thereby mask the relatively high stability of their furanose forms. hilore effective hydrogen bonding with \\later is also regarded as a factor that should stabilize /3-pyranoses (equatorial OH-1) more than the a-anomers (3,12). In attempting to relate the observed changes in equilibrium in the t\vo solvents with such hydrogen-bonding possibilities and with structural features that inight be common to, for example, arabinose and mannose, one or two possibilities suggest themselves.…”
mentioning
confidence: 99%
“…4). Kabayama & Patterson ( 1958), Tait et al (1972) and Uedaira et a/ ( 1989) independently reported that there was a close correlation between hydration and the number of equatorial -OH groups or the number of dynamic hydration in reducing sugars. The slight difference in the curve of glucose In Fig.…”
Section: Resultsmentioning
confidence: 99%